Effects of accountants' job satisfaction and affective commitment on turnover intentions - Tair, Muhannad Abu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2012)
ABSTRACT: This study investigates effect of job satisfaction and affective commitment on accountants’ turnover intentions in Turkish Republic of North Cyprus. Accounting firms in Lefkoşa and Magosa which are two of the biggest cities in Turkish Republic of Northern Cyprus were targeted for gathering data using questionnaire method. Likert type scale questions regarding job satisfaction, affective commitment, turnover intention and demographic information were asked to the respondents. A total of 80 questionnaires were developed and distributed in 8 accounting firms. Of these questionnaires only 43 usable questionnaires were elicited, making 54% response rate. Then the data were analyzed using Partial Least Squares (PLS) to investigate job satisfaction and affective commitment of accountants so as to uncover the relation between the two and their effects on job turnover intentions. In this study, three hypotheses was developed. Firstly, we hypothesize that there is a positive relationship between accountants’ job satisfaction and affective commitment. Secondly, it is hypothesized that there is a negative relationship between accountants’ job satisfaction and turnover intention. Finally, we hypothesize that accountants’ affective commitment has a significant negative effect on turnover intention. The results of the current study reveal that job satisfaction has a statistically significant negative influence on accountants’ intention to quit. On the other hand, the findings demonstrate that affective commitment does not influence accountants’ turnover intentions. This finding is not consistent with the hypothesized relationship as stated in the previous literature. The structural model results further reveal that job satisfaction derived from a job has a statistically significant positive association with accountants’ affective commitment. Keywords: Job Satisfaction, Affective Commitment, Turnover Intention, North Cyprus, Accountants’. Intention to Quit. ………………………………………………………………………………………………………………………… ÖZ: Bu tez çalışmasında iş tatmini ve duygusal bağlılığın Kuzey Kıbrıs Türk Cumhuriyetindeki muhasebecilerin iş bırakma eğilimleri üzerindeki etkileri incelenmiştir. Çalışma için gerekli veriler anket yöntemiyle toplanmıştır. Veriler Kuzey Kıbrıs Türk Cumhuriyetinin iki büyük şehri olan Lefkoşa ve Gazi Magosada faaliyet gösteren 8 muhasebe firmasından toplanmıştır. İş tatmini, duygusal bağlılık , işten ayrılma eğilimleri ve demografik özelliklerle ilgili sorular içeren toplan 80 adet anket dağıtılmıştır. Dağıtılan 80 anketten ise sadece 43 adet kullanılabilir anket elde edilmiştir, bunun anlamı da %54’lük geri dönüm oranının olduğudur. Toplanan veriler PLS programı kullanılarak analiz edilmiştir. Bu tez çalışmasında 3 adet hipotez geliştirilmiştir. Birinci hipotezde muhasebecilerin iş tatmini ile duygusal baklılıkları arasında olumlu bir ilişki olduğu varsayılmıştır. İkinci hipotezde muhasebecilerin iş tatmini ile işten ayrılma eğilimleri arasında negatif bir ilişki olduğu varsayılmıştır. Üçüncü hipotezde ise muhasebecilerin duygusal bağlılıkları ile işten ayrılma eğilimleri arasında negatif bir ilişki olduğu varsayılmıştır Yapılan analizler sonucunda muhasebecilerin iş tatmiini ile işten ayrılma eğilimleri arasında negatif bir ilişki olduğu ortaya çıkmıştır. Duygusal bağlılık ile işten ayrılma eğilimleri arasında ise herhangi bir ilişki bulunamamaıştır. İş tatmini ile duygusal bağlılık arasında ise pozitif bir ilişki bulunmuştur. Anahtar Kelemiler: İş doyumu, Duygusal bağlılık, Ayrılma niyeti, Kuzey Kibris,Muhasebeciler, Bırakmak niyeti.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2012. Supervisor: Assoc. Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Employee Motivation - Job Satisfaction - Accounting Sector - Cyprus, North; Job Satisfaction Affective Commitment Turnover Intention North Cyprus Accountants Intention to Quit